1996
DOI: 10.1088/0953-4075/29/16/009
|View full text |Cite
|
Sign up to set email alerts
|

Coherent control in four-photon excitation schemes

Abstract: We report the observation of coherent control of the ionization rate in four-photon resonant, five-photon ionization schemes in Kr and Xe. The intermediate resonance is excited via different interfering channels involving four-photon absorption of the fundamental laser frequency ( ionization) as well as one third harmonic and one fundamental frequency photon absorption ( excitation), a particular aspect of the scheme being that interference occurs at a virtual level. By varying the relative phase of the two el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 26 publications
(18 reference statements)
0
14
0
Order By: Relevance
“…3. Four-photon generalized ionization cross section σ (4) , leading to 1 S e (full line), 1 D e (dotted line) and 1 G e (dashed line) continua from the ground state of Mg, as a function of the photoelectron energy.…”
Section: Table -Figure Captionsmentioning
confidence: 99%
See 1 more Smart Citation
“…3. Four-photon generalized ionization cross section σ (4) , leading to 1 S e (full line), 1 D e (dotted line) and 1 G e (dashed line) continua from the ground state of Mg, as a function of the photoelectron energy.…”
Section: Table -Figure Captionsmentioning
confidence: 99%
“…The aspect in question is the possibility of altering the line shape of an autoionizing resonance through such phase control. The general features of phase control in photoabsorption have been discussed in the literature extensively [1,2,3,4,5,6,7]. The possibility of altering an autoionizing line shape has also been discussed [8] to some extent in theoretical work where it has been shown that one particularly intriguing feature, depending on parameters, is the possibility of turning off the transition to the "discrete" or the continuum part of the resonance [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…25 Early experiments used coherent phase control to transfer population from one bound state to another. [26][27][28][29][30] More challenging, and of greater chemical interest, is the control over bound-to-continuum transitions. To date, coherent control has been demonstrated for the ionization of atoms 31 and molecules, 31,32 the photodissociation of molecules, 33,34 and the switching of photocurrents in semiconductors 35,36 and photocathodes.…”
Section: Experimental Tests Of Coherent Controlmentioning
confidence: 99%
“…The latter corresponds to control of photoionization and photodissociation yields. There are only very few experiments dealing with coherent control of frequency conversion [5][6][7].…”
Section: Introductionmentioning
confidence: 99%